1993
DOI: 10.1136/jmg.30.3.235
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary anaemias in Portugal: epidemiology, public health significance, and control.

Abstract: A countrywide prospective study aimed at establishing the prevalence of the haemoglobinopathy genes in the Portuguese population was carried out by screening 15 208 randomly selected blood samples from young males. This male based survey provided the opportunity of assessing simultaneously the prevalence of the red cell enzyme glucose-6-phosphate dehydrogenase (G6PD) deficiency, thus giving a picture of these important hereditary anaemias in Portugal.The results showed a low average frequency of a thalassaemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
5

Year Published

1995
1995
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 7 publications
3
24
0
5
Order By: Relevance
“…Following a study of prevalence of G6PD deficiency in the universal male conscription for military service in Portugal (n ϭ 13785), Martins et al found a prevalence of 0.51 Ϯ 0.109 (5). The frequency of G6PD deficiency-conferring genes in the male population of Portugal determined by our study is 0.39 (Table 5).…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…Following a study of prevalence of G6PD deficiency in the universal male conscription for military service in Portugal (n ϭ 13785), Martins et al found a prevalence of 0.51 Ϯ 0.109 (5). The frequency of G6PD deficiency-conferring genes in the male population of Portugal determined by our study is 0.39 (Table 5).…”
Section: Resultssupporting
confidence: 57%
“…The G6PD AϪ mutation is present in the north, center and south. The predominance of mutations in genes G6PD A 376 A 3 G FokI (ϩ) in Portugal, 75.7% (25/33), is most likely the consequence of the past miscegenation between the Negroid and Caucasoid groups as previously described for sickle cell anemia (5,19,20).…”
Section: Tablementioning
confidence: 54%
See 1 more Smart Citation
“…Due to the geographic heterogeneity of C282Y mutation in Portugal (Cardoso et al 2001), and being that the beta-thalassemia trait is more frequent in the southern part of the country (Martins et al 1993), all individuals studied were of southern Portugal origin. Diagnosis of the beta-thalassemia trait was defined by low mean corpuscular volume (MCV <80 fl), low mean corpuscular hemoglobin (MCH <27 pg), and increased HbA2 (>3.5%).…”
Section: Subjectsmentioning
confidence: 99%
“…The beta-thalassemia trait, moderately common in the southern Portugal population (Martins et al 1993), is characterized by mild, ineffective erythropoiesis that can induce excess iron absorption and ultimately lead to iron overload (Weatherall and Clegg 1981). Since only a minority of patients develop iron overload, the hypothesis that genetic modifiers may be related to this phenotypic variability has been set Weatherall 2001).…”
Section: Introductionmentioning
confidence: 99%